Evaluation of Traffic Safety with Biodiesel Fuel: A Study Based in Hong Kong - YANG MAOLIN, YANG MAOLIN; NIZAMUDDIN INAMDAR, DR MOHAMMAD NIZAMUDDIN INAMDAR; BINTI RASHD, DR NUR SYAZA BINTI RASHD (International Journal of Multidisciplinary Research and Studies, 2024)
As a result of the "Because of the impending implementation of new emission regulations, the car industry is hard at work perfecting new engine management systems and pollution control technology. The European Regulation for Heavy-Duty Diesel Vehicle Emissions Limits was the inspiration for this concept back in 1992. (Euro-I). The Euro-II standard was introduced in 1996, while the Euro-III standard was implemented in 1999. As new energy sources and technologies become available, stricter standards are expected to be implemented in 2005 (Euro-IV) and 2008. (Euro-V). Poor vehicle maintenance is a common cause of excessive emissions from automobiles. Inspection and maintenance (I&M) programmes are the most reliable method for identifying high emitters within a fleet of currently operating vehicles. In addition, civic and vocational education are essential for promoting safe driving practises and increasing employment rates "automobile maintenance and repair shop Over in Japan and the US, "In most U.S. states, diesel vehicles, whether new or old, are subject to comparable restrictions, but testing procedures vary. HKEPD has mandated that all vehicles in Hong Kong comply to an emission and noise standard. In addition to preventing the spread of smoke, annual inspection and testing of emissions is also a part of "Projects in Instruction and Management. Cars, trucks, and buses currently on the road "fleets' emissions are tracked and analyzed. These mandated rules do more than only reduce pollution from cars' exhaust systems; they also help save a lot of money by promoting more efficient car design "combustion.